Are Individual Investors Attracted to Shareholder Perks in the Emerging Markets? An Experimental Study in Indonesia - Trihermanto, Febi; Nainggolan, Yunieta Anny; Matsuura, Yoshiyuki (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
Abstract. Choice-Based Conjoint (CBC) analysis experiment is conducted in this study to investigate perception equivalency of shareholder perks (SP) and dividend policy among Indonesian investors and to examine whether SP as a new alternative of payout policy can attract more individual investors in Indonesia. The results show that investors prefer SP over dividend in both 2 and 4 percent yield. However, the marginal utility of SP is decreasing to yield. This result suggests that individual investors prefer to receive SP rather than no dividends but they do not expect to receive an excessive number of SP when it is possible for the company to distribute a high amount of cash dividend. Furthermore, the results grouped by gender indicates that female respondents are prefer SP to dividend and have a higher economic value on SP than their male counterpart. Practically, by investing in an SP-paying stocks, individual investors are able to buy their favourite brands and products at lower prices which might be more beneficial than receiving a small amount of cash dividends. Meanwhile, for companies, the results imply that the distribution of SP can attract a number of individual investors, particularly women. Keywords: Shareholder Perks, Dividend Policy, Individual Investor, Conjoint Analysis, Indonesia